Recent advances in EST sequencing in Crassostrea gigas: towards the sequencing of the Pacific oyster genome - Boudry, Pierre; Huvet, Arnaud; Lapegue, Sylvie; Sauvage, Christopher; Tanguy, A.; Moraga, D.; Goostrey, A.; Prunet, P.; Boulo, Viviane; Gueguen, Y.; Moal, Jeanne; Fleury, Elodie; et al. (Marine Genonics Europe Exploratory Workshop, 2007)
Rationale for EST and genome sequencing of the Pacific oyster: • its membership of the Lophotrochozoa, an little studied branch of the Eukaryotes, • its worldwide aquacultural importance (4.2 million metric tons, worth 3.5 billion US dollars), • its high fecundity, with concomitantly high DNA polymorphism, • its use as a biosensor of coastal pollution. In 2004, an international community of biologists, the Oyster Genome Consortium (OGC) led by D. Hedgecock (University of Southern California) and uniting 70 participants from 10 countries, first presented the Pacific oyster Crassostrea gigas as a genome-sequencing candidate to Joint Genome Institute (JGI, USA) (Hedgecock et al., 2005). Besides this project (that remains to be accepted), several EST sequencing projects have been successfully initiated at JGI, Genoscope (France) and the Max Planck Institute (Germany). These will considerably enlarge the first public database specifically dedicated to C. gigas (Gueguen et al., 2003; www.ifremer.fr/GigasBase).